Post-collisional alkaline magmatism as gateway for metal and sulfur enrichment of the continental lower crust. (15th February 2018) - Fiorentini, Marco L.; LaFlamme, Crystal; Denyszyn, Steven; Mole, David; Maas, Roland; Locmelis, Marek; Caruso, Stefano; Bui, Thi-Hao
Abstract: Mafic and ultramafic magmas that intrude into the lower crust can preserve evidence for metal and sulfur transfer from the lithospheric mantle into the lower continental crust. Here we focus on a series of ultramafic, alkaline pipes in the Ivrea Zone (NW Italy), which exposes deeply buried (6–11 kbar), migmatitic metasedimentary rocks intruded by voluminous basaltic magmas of the Mafic Complex, a major crustal underplating event precisely dated via U/Pb CA-IDTIMS on zircon at 286.8 ± 0.4 Ma. The ultramafic pipes postdate the Mafic Complex and from 100 to 300 m wide cumulate-rich conduits. They are hydrated and carbonated, have unusually high incompatible element concentrations and contain blebby and semi-massive Ni-Cu-PGE sulfide mineralisation. The sulfides occur as coarse intergranular nodules (>10 mm) and as small intragranular blebs (<1 mm) hosted in olivine, and have homogeneous, mantle-like δ 34 S (+1.35 ± 0.25‰). This homogeneity suggests that the pipes reached sulfide supersaturation without addition of crustal sulfur, and that the δ 34 S signature is representative of the continental lithospheric mantle. One of the pipes, the 249 Ma Valmaggia pipe, carries a very distinctive Sr-Nd-Hf-Pb isotopic composition in its core ( 87 Sr/ 86 Sr 0.70250, εNd-18, εHf-18, 206 Pb/ 204 Pb 16.0, 207 Pb/ 204 Pb 15.16, 208 Pb/ 204 Pb 35.87), very different from the margin of this pipe and from other pipes that have higher 87 Sr/ 86 Sr, εNd and 206 Pb/ 204 Pb. The unusual isotopic composition of the Valmaggia pipe requires a source with long-term (2500–1500 million years) U-, Th- and Rb-depletion and LREE enrichment. Such compositions are found in Late Archean/Early Proterozoic granulites and lower crustal xenoliths. We suggest that the unusual isotopic composition of the Valmaggia pipe reflects contamination of the mantle source of the pipe with a crustal component that is neither represented in the local Paleozoic crust nor in the isotopically anomalous hydrated mantle inferred as the source of the large-volume mafic underplate that formed the Mafic Complex. During post-collisional gravitational collapse of the Variscan Orogen, this source produced the alkaline, metal (Ni, Cu, PGE)- and volatile (H2 O, CO2, S)-rich mafic–ultramafic magma that formed the deep-crustal intrusion at Valmaggia. U/Pb dating of other chemically and geologically comparable pipes in the area shows that this process was active over at least 40 Ma. The Ivrea pipes illustrate how the lower continental crust can be fertilised with mantle-derived metals and volatiles, which are available for later remobilisation into upper-crustal ore systems. World-class mineral deposits along the margins of lithospheric blocks may thus be the result of both favourable crustal architecture (focussing of magmas and fluids) and localised volatile and metal enrichment of the lower crust related to mantle-derived hydrous metasomatism.